The relationship between clinical trial participation and inhaler technique errors in asthma and COPD patients - Perumal, Rubeshan (Department of Medicine, 2021)
Background Incorrect inhaler use is associated with poorer health outcomes, reduced quality of life, and higher healthcare utilisation in patients with asthma and COPD. Method We performed an observational study of pressurized metered-dose inhaler technique in patients with asthma or COPD. Patients were assessed using a six-point inhaler checklist to identify common critical inhaler technique errors. An inadequate inhaler technique was defined as the presence of one or more critical errors. A multivariate logistic regression model was used to determine the odds of an inadequate inhaler technique. Results During the 14-month study period, 357 patients were enrolled. At least one critical error was executed by 66.7% of participants, and 24.9% made four or more critical errors. The most common errors were: failure to exhale completely prior to pMDI activation and inhalation (49.6%), failure to perform a slow, deep inhalation following device activation (48.7%), and failure to perform a breathhold at the end of inspiration (47.3%). The risk of a critical error was higher in COPD patients (aOR 2.25, 95%CI 1.13 – 4.47). Prior training reduced error risk specifically when trained by a doctor (aOR 0.08, 95% CI 0.1 – 0.57) or a pharmacist (aOR 0.02, 95% CI 0.01 – 0.26) compared to those with no training. Previous clinical trial participation significantly reduced error risk and rate:< 3 trials (aOR 0.35, 95% CI 0.19 – 0.66) and ≥3 trials (aOR 0.17, 95% CI 0.07 – 0.42). The rate of critical errors was not significantly associated with age, sex, or prior pMDI experience. Conclusion This study found a high rate of critical inhaler technique errors in a mixed population of asthma and COPD patients; however, prior training and in particular, multiple previous clinical trial participation significantly reduced the risk of errors.